2010
DOI: 10.1111/j.1472-765x.2010.02840.x
|View full text |Cite
|
Sign up to set email alerts
|

A real-time PCR-based strategy for the detection of Paenibacillus larvae vegetative cells and spores to improve the diagnosis and the screening of American foulbrood

Abstract: Aim:  To develop a real‐time PCR‐based strategy for the detection of Paenibacillus larvae vegetative cells and spores to improve the diagnosis and the screening of American foulbrood (AFB), the most harmful pathology of honeybee brood. Methods and Results:  A real‐time PCR that allowed selective identification and quantification of P. larvae 16S rRNA sequence was developed. Using standard samples quantified by flow cytometry, detection limits of 37·5 vegetative cells ml−1 and 10 spores ml−1 were determined. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 24 publications
1
36
1
Order By: Relevance
“…Incubation of the samples in a rich nutrient medium for 1 h at 37°C considerably improved the protocol, presumably because the spore envelope is altered and the bacterial DNA has become more accessible for extraction. Martinez et al (2010) reported an assay detection limit of 2 P. larvae spores g −1 honey contrasting to earlier reports of a detection limit of 10 5 spores g −1 of honey (Ryba et al 2009) and 283 spores g −1 of honey (Alippi et al 2004). These differences may very well be due to differences in extraction methods, highlighting the possibility that comparative evaluation of DNA extraction and purification may be more important than comparisons of different amplification methods.…”
Section: Discussioncontrasting
confidence: 49%
See 4 more Smart Citations
“…Incubation of the samples in a rich nutrient medium for 1 h at 37°C considerably improved the protocol, presumably because the spore envelope is altered and the bacterial DNA has become more accessible for extraction. Martinez et al (2010) reported an assay detection limit of 2 P. larvae spores g −1 honey contrasting to earlier reports of a detection limit of 10 5 spores g −1 of honey (Ryba et al 2009) and 283 spores g −1 of honey (Alippi et al 2004). These differences may very well be due to differences in extraction methods, highlighting the possibility that comparative evaluation of DNA extraction and purification may be more important than comparisons of different amplification methods.…”
Section: Discussioncontrasting
confidence: 49%
“…A pilot experiment was performed to evaluate two previously published extraction protocols for isolating genomic bacterial DNA from P. larvae spores (Martinez et al 2010;Ryba et al 2009). A stock spore suspension of P. larvae (CCUG 48979 Forsgren et al 2008) spores/mL) of the suspension were prepared.…”
Section: Comparison Of Dna Extraction Methodsmentioning
confidence: 99%
See 3 more Smart Citations